Carotid intima-media thickness, hypertension, and dyslipidemia in obese adolescents - Widjaja, Nur Aisiyah (Pan Afr Med J, 2019)
INTRODUCTION: Obesity is a global health problem with growing prevalence in developing countries. Obesity causes chronic inflammation due to imbalances between pro- and anti-inflammatory cytokines. This causes metabolic complications such as dyslipidemia, hypertension, and cardiovascular disorder. Carotid intima–media thickness (CIMT) is a predictor of atherosclerosis which could be measured easily and non-invasively. Early detection of cardiovascular diseases in obese adolescents at risk is hoped to improve outcomes. METHODS: This is a cross-sectional study on obese adolescents aged 13-16 year old at Pediatric Clinic of Dr. Soetomo General Hospital. Obesity is defined as Body mass index higher than 95(th) percentiles according to CDC (2000). Dyslipidemia is diagnosed when either an increase in cholesterol, LDL, triglyceride or a decrease in HDL level is found, as recommended by NCPE and American Academy of Pediatrics. Hypertension is defined as an increase of blood pressure > P95 according to age and gender. The differences of CIMT based on dyslipidemia, hypertension, and gender were analyzed with Wilcoxon Mann Whitney with significant p value (p < 0,005). RESULTS: This study included 59 obese adolescents, consisting of 32 (54.2%) male adolescents and 35 (59.3%) female adolescents. Dyslipidemia was found on 38 (64.4%) adolescents and hypertension was found on 35 (59.3%) adolescents. No difference of CIMT was found between obese adolescents with and without dyslipidemia and with and without hypertension based on gender (p > 0.05). CONCLUSION: No difference of CIMT based on gender between adolescents aged below 18. The high number of dyslipidemia and hypertension in obese adolescents need an early detection of cardiovascular complication.